Impact on water sources due to land use and land cover change in Chitwan district, Nepal - Poudel, Moti; Sharma, Subodh; Ghimire, Anish; Howard, Guy; Joshi, Prayon (Kathmandu University Journal of Science Engineering and Technology, 2024)
Rapid urbanization and unplanned infrastructures are stressing the drinking water sources, primarily due to land use and land cover changes (LULCC). Rapid population increases water demand and is straining water resources. This study aims to analyze LULCC from 1991 to 2020 and explore its impact on 23 regular used drinking water sources in Ratnanagar and Kalika municipality in Chitwan district. ArcGIS 10.8 classified five different classes in the images compiled from Landsat 5 and 8. Supervised classification with Maximum Likelihood algorithm was used with 30 signatures for each class as training samples. After the calculation of producer's accuracy and user's accuracy, accuracy assessment of classified images based on the ground truth points in 2020 Google earth images shows that kappa coefficient was 0.892 and overall accuracy was 91.67%. Over a period of 30 years, tree cover, agricultural, and water body areas have decreased by 15.18 %, 2.94 %, and 0.08 %, respectively while built-up and barren land have increased by 7.09 % and 11.11 % correspondingly. Secondary data from 30 years shows the population growth in study area was about 400% and 337.12 mm per decade reduction of precipitation. Increased built-up area has reduced the surface area for percolation of water. Uncontrolled LULCC, urbanization, and local climatic phenomenon have threatened the drinking water sources. Implementing the principles of resilient and sustainable urbanization, sustainable land use practices, climate resilient water safety tools and adequate investment in water sources protection can be a sustainable approach to address LULCC.